(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Stress in learning is a feeling faced by someone when there is pressure on them. The purpose of this study was to determine whether there is an influence of PJOK lessons in reducing the level of learning stress in class VIII students of SMP N 4 Kunto Darussalam. This study used a survey method with a quantitative descriptive approach; the target population was all class VIII students of SMP N 4 Kunto Darussalam. The number of research participants was 113 students. The sample in this study was 88 students who were determined using the technique of nonprobability sampling with the Slovin formula. The instrument used is a questionnaire. Contains 4 alternative answers taken through a Likert scale.The results of the research that has been carried out show that The Effect of Physical Education Lessons in Reducing the Level of Learning Stress in Class VIII Students of SMP N 4 Kunto Darussalam in the category of "very high" 24% of samples The Effect of Physical Education Lessons in Reducing the Level of Learning Stress in Students (21 students), in the category of "very high" 36% of samples The Effect of Physical Education Lessons in Reducing the Level of Learning Stress in Students (32 students), in the category of "High" 7% of samples The Effect of Physical Education Lessons in Reducing the Level of Learning Stress in Students (6 students), in the category of "moderate" 14% of samples The Effect of Physical Education Lessons in Reducing the Level of Learning Stress in Students (12 students), in the category of "sufficient" 13% of samples The Effect of Physical Education Lessons in Reducing the Level of Learning Stress in Students (11 students), in the category of "low" 6% of samples The Effect of Physical Education Lessons in Reducing the Level of Learning Stress in Students (5 students) and in the category of "very low" 1% of samples The Effect of Physical Education Lessons in Reducing the Level of Learning Stress in Students (1 student). Based on the description above, it can be concluded that from the 7 categories to determine how the influence of PJOK lessons in reducing the level of learning stress in students of SMP N 4 Kunto Darussalam, the highest results were obtained, namely around 36% (32 students) of respondents who had a "very high" influence of PJOK lessons in reducing the level of student learning stress.